(untitled) (Impact: Journal of Transformation, 2019)
The English language plays a key role in Nigeria. It is a major means by which knowledge is impacted. As a result of the advancement in technology, the language has gained more recognition and has improved communication worldwide. However, many users especially the youths have abused the use of social networking. In the past, the poor performance of students in written English was attributed to inadequate motivation, teaching and learning environment, and lack of facilities. Today, other factors have emerged as a result of technological advancement and the internet. The spelling system of English is a major problem for the second language user community. New forms of written expressions among youths now compound this. The question is: what are the effects of social media on students’ writing? The question was answered through a comparative review of the written text in social media and academic settings. Samples of Nigerian youths’ written texts were collected via social media platforms, in addition to paragraph essays from various students in selected schools in Lagos. Findings indicate that youths use new forms of expressions in their social communication, which may not be understood by the older generation. Youths also do not abide by the grammatical rules in both formal and informal writings as reflected in their writings. Therefore, it is recommended that formal and non-formal writings should be taught comparatively in the classrooms to increase awareness of the new forms of expressions that infiltrate academic writings. Also, for a good quality of education to be promoted in Nigeria, teachers should discourage these new forms of technological expression among youths.